Testing the resolving power of two-dimensional K+K+ interferometry - Padula, Sandra S. [UNESP]; Roldão, Cristiane G. [UNESP] (American Physical Society (APS), 1998)
We show results from an analysis performed to test the resolving power of a two-dimensional χ2 method proposed previously when applied to the case of kaon interferometry, where no significant contribution from long-lived resonances is expected. For that purpose, use is made of the preliminary E859 K+K+ interferometry data from Si+Au collisions at 14.6/4 GeV/c. Although less sensitivity is achieved in the present case, this analysis seems to favor scenarios with no resonance formation at the AGS energy range. The possible compatibility of data with zero decoupling proper time interval, conjectured by the three-dimensional experimental analysis, is also investigated and is ruled out when considering more realistic dynamical models with expanding sources. Furthermore, these results strongly emphasize that the static Gaussian parametrization cannot be trusted under more realistic conditions, leading to a distorted or even wrong interpretation of the source parameters.